Prevalence and factors associated with anaemia among pregnant women in rural Mysore, Karnataka, India - Siddalingappa, Hugara; M. R., Narayana Murthy; N. C., Ashok (International Journal Of Community Medicine And Public Health, 2016)
Background: Under nutrition of pregnant women has been an important aspect of maternal health. Anemia is one of the important conditions which have to be screened among them. If not treated, it can lead to maternal and foetal complications sometimes ending in death. Anemia can also indicate the operational efficiency of Maternal and Child Health facilities in the community. Objective of the study was to assess the prevalence and factors associated with anemia among pregnant women in rural field practice area of a private Medical College. Methods: This cross sectional community based study was conducted in Hadinaru primary health centre (PHC), of Mysore district for a period of 6 months (June to November 2011). Pregnant women who delivered between Janauary to December 2010 and were permanent residents of the villages under Hadinaru PHC were included in the study. These mothers were visited at their home and information was collected using pre-structured questionnaire. Lab reports and antenatal check-up details were referred wherever available. Results: 314 mothers were covered in the study out of which 196 were anemic (62.4%). Mild anemia was seen in 52.0% women and 11.0% had moderate anemia. Weight gain during pregnancy and menstrual problems of mothers were significantly associated with anemia during pregnancy. Conclusions: The prevalence of anaemia among pregnant women was found to be 62.4%. Even though there were no cases of severe anaemia, mild and moderate degree anemics were in significant number.